Hubungan Pembelajaran Online Dengan Kejadian Stres Pada Mahasiswa Di Fakultas Ilmu Kesehatan Universitas Islam As-Syafi’iyah Pada Masa Pandemi Covid-19 - Ade Ajeng Tianti; Muhamad Idris (Jurnal Afiat : Kesehatan dan Anak, 2021)
Based on the circular letter of the Ministry of Education and Culture (Kemendikbud) Directorate of Higher Education No. 1 year 2020 during the covid-19 pandemic, universities eliminated teaching and learning activities on campus and shifted them to distance learning (online). In online learning at the Faculty of Health Sciences As-Syafi'iyah Islamic University the implementation of online lectures raises several obstacles such as the internet network and assignments that become stressors for students. The purpose of the study was to determine the relationship between online learning and the incidence of stress in students at the Faculty of Health Sciences, As-Syafi'iyah Islamic University during the Covid-19 pandemic. The research method used descriptive correlation with a cross sectional approach, a population of 184 students consisting of semesters 2, 4, and 6. The sample uses the slovin formula to 65 students taken by proportional sampling technique. The analysis used univariate and biavariate using Chi-Square test = 5% (0.05). The results of the univariate analysis (%) showed a good picture of online learning 55.4% and the incidence of stress was 43.1%, bivariate analysis obtained p or Asym values. Sig. (2-sided) = 0.209 with a value of = 5% (0.05). The conclusion is that there is no relationship between online learning and the incidence of stress in students at the Faculty of Health Sciences, As-Syafi'iyah Islamic University during the Covid-19 pandemic. Suggestions are that students are expected to be more active in class forums such as asking about material that has not been understood and activating the zoom camera.